Lipid metabolism in streptozotocin induced experimental diabetes and it’s correction with niacin-oxyethylidendiphosphonatogermanate - N. V. Kresyun; А. А. Son; V. V. Godovan; L. S. Godlevsky (Zaporožskij Medicinskij Žurnal)
Introduction. The development of approaches for effective control of diabetes-induced deterioration of lipid metabolism and plasma glucose level could be implemented by the applying of germanium-contained biologically active substances. Among others such compound as niacin – oxyethylidendiphosphonatogermanate (MIGU-4) should be mentioned, which is able to correct effectively the lipid layers of liver mitochondrial membranes on models of streptozotocin – induced diabetes.